The Iranian Involvement in the Yemeni War - Taha, Lynne (2022)
The rivalry between Saudi Arabia and Iran has been one of the main causes of the conflicts and wars in the Middle East since decades. Lebanon, Iraq, and Syria, were places where the two states competed aggressively to bring them under their hegemony. The latest Yemini civil war intensified this rivalry and both countries are now deeply involved in this civil war. It is interesting to notice that historically Iran’s involvement in Yemen was not as intense as Saudi Arabia’s. Yemen has never been an urgent priority for Iran, unlike Saudi Arabia that considers Yemen as the backyard of the Kingdom. Accordingly, this thesis seeks to understand the reasons why Iran has become so interested in the latest conflict in Yemen. Although Yemen had always provided opportunities to Iran to intervene in its internal affairs - such as civil wars and the presence of a Shia Houthi community - this thesis tries to answer the following research questions: Why has Yemen now become a priority to Iran? What are the tools that Iran is using to achieve its objective in Yemen? On that basis and by using a neorealist lens, this thesis reveals that Iran has decided to change its foreign policy towards Yemen as it has found a golden opportunity to strengthen its alliance with the Houthis, amidst the political chaos in the country to achieve its greater geopolitical objectives. This study shows that the Iranian involvement in Yemen is linked to its quest to strengthen its influence in the Middle East by geographically encircling its regional main opponents such as Saudi Arabia and the Gulf States with countries that are dominated by its allies. Furthermore, bringing these states that have a strategic geographical location under its control will allow it to exert pressure on the US and give it a strategic military advantage if it was to be attacked by the US and its Western allies. Iran had managed to have strong influence in Lebanon, Syria and Iran. Now it is the turn of Yemen.